PERSEPSI GURU AL-QUR’AN HADIST DALAM IMPLEMENTASI KURIKULUM 2013 PADA MATA PELAJARAN AL-QUR’AN HADIST DI MTS NEGERI AMBON - Harsono Harsono (IAIN Ambon, 2021)
Abstract: The success or failure of an education, whether or not a student and educator are able to absorb and provide teaching, and the success or failure of an educational goal that is achieved will certainly depend on the curriculum. If the curriculum is designed systematically and comprehensively as well as integral to all the development and teaching needs of students to prepare themselves for life. This type of research is a qualitative research. The subjects in this study were 3 teachers with data collection techniques in the form of observation, interviews, and documentation with the research instrument being the researcher himself in obtaining field data. The results of this study indicate that the perception of Al-Qur'an Hadith teachers in the implementation of the 2013 curriculum regarding the planning of Al-Qur'an Hadith learning at MTs Negeri Ambon between Al-Qur'an Hadith teachers with one another is not the same where everyone has their own way. different points of view, so that in planning the 2013 curriculum on the subjects of Al-Qur'an Hadith in the form of readiness carried out by teachers to implement the 2013 curriculum at this stage how is the readiness for lesson plans and syllabus and most importantly must learn more about making KI and KD mapping and in accordance with the Minister of Education and Culture No. 24 of 2016. So that the supporting factors of 2013 curriculum planning in Al-Qur'an Hadith are given the opportunity to learn how to develop an ongoing curriculum, because 2013 curriculum planning is able to shape children's character for the better. The inhibiting factors faced by Al-Qur'an Hadith teachers in learning with the implementation of the 2013 curriculum include preparations from various parties that have not met the demands of the curriculum itself, seem rushed and have not been prepared properly, judging from the distribution of the books needed only arrived after the material is too much. Keywords: Teacher Perception, Curriculum 2013 Abstrak: Berhasil tidaknya suatu pendidikan, mampu tidaknya seorang peserta didik dan pendidik dalam menyerap dan memberikan pengajaran, dan sukses tidaknya suatu tujuan pendidikan itu dicapai tentu akan sangat berpulang kepada kurikulum. Bila kurikulumnya didesain dengan sistematis dan komprehensif serta integral dengan segala kebutuhan pengembangan dan pengajaran anak didik untuk mempersiapkan diri menghadapi kehidupannya. Tipe penelitian ini adalah penelitian kualitatif, Subjek dalam penelitian ini adalah 3 orang guru dengan teknik pengumpulan data berupa observasi, wawancara, dan dokumentasi dengan instrumen penelitian adalah peneliti sendiri dalam memperoleh data-data lapangan. Hasil penelitian ini menunjukan bahwa Persepsi guru Al-Qur’an Hadist dalam implementasi kurikulum 2013 tentang perencanaan pembelajaran Al-Qur’an Hadist di MTs Negeri Ambon antara guru Al-qur’an Hadist yang satu dengan yang lainnya tidaklah sama dimana setiap orang memiliki cara pandang yang berbeda, sehingga pada perencanaan kurikulum 2013 pada mata pelajaran Al-Qur’an Hadist berupa kesiapan yang dilakukan oleh para guru untuk melaksanakan kurikulum 2013 pada tahap ini bagaimana kesiapan terhadap RPP dan silabus dan yang terpenting harus belajar lebih mengenai pembuatan pemetaan KI dan KD serta sesuai dengan permendikbud No. 24 Tahun 2016. Sehingga Faktor pendukung dari perencanaan kurikulum 2013 pada Al-Qur’an Hadist diberikan kesempatan untuk belajar bagaimana cara mengembangkan kurikulum yang sedang berjalan, karena dalam perencanaan kurikulum 2013 mampu membentukkan karakter anak menjadi lebih baik. Faktor penghambat yang dihadapi oleh guru Al-Qur’an Hadist dalam pembelajaran dengan implementasi kurikulum 2013 meliputi persiapan dari berbagai pihak belum memenuhi tuntutan dari kurikulum itu sendiri, terkesan tergesa-gesa dan belum disiapkan dengan matang, dilihat dari distribusi buku yang dibutuhkan baru datang setelah materinya terlampaui. Kata kunci: Persepsi Guru, Kurikulum 2013